Greening a Brazilian cotton seed processing company: from challenges to strategic opportunities - Teixeira, Adriano Alves [UNESP]; Bello, Vinicius Fernando; Teixeira, Talita Borges [UNESP]; Jabbour, Charbel José Chiappetta [UNESP]; Oliveira, Jorge Henrique Caldeira de (Emerald, 2013)
This paper aims to shed light on a current and important theme that has been gaining increasing importance for governments, society and companies: the greening of agricultural companies in developing countries. The research objective is to classify a Brazilian cotton seed processing company in the evolutionary stages of environmental management: reactive, preventive or proactive. Design/methodology/approach– A case study was conducted in a Brazilian cotton seed processing company.Findings– The main results are: the studied company is positioned in the preventive stage of environmental management; this company is investing in operational green practices; environmental management in this company is motivated by various factors aiming at an increased competitive advantage. Finally, it can be concluded that this company is looking for green opportunities towards the proactive environmental management stage.
Keywords: Agricultural management; Cottonseed processing; Green management; Environmental management; Brazil; Agriculture